ANALYZING TRANSLATION METHOD IN SONG LYRIC “MEMORIES” MAROON 5 FROM ENGLISH TO INDONESIAN - KEZIA DEBORA PURBA; MITHA MANURUNG; FYOLITA ARITONANG; CINDY SILITONGA; SELVIANA NAPITUPULU (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2022)
This study contains an analysis of translation method in the song lyric “Memories” by Maroon 5 which translated by asaljeplak.com. In translation analysis processes, the researcher used theory of translation method based on Newmark’s theory, they were word-for-word translation, literal translation, faithful translation, semantic translation, adaption, free translation, idiomatic translation, communicative translation. This study used qualitative descriptive method in analyzing the data. Problem discussed in this research were : 1. What is the meaning of the song lyric “memories” into Indonesian? 2. What translation method that translator used to translate the song lyric “memories” into Indonesian? Finally, the researcher found the translation method that is used by translator of song lyric “Memories” they are 11 or 50% belongs to word-for-word translation, there are 3 or 13.6% data belong to literal translation, there are 2 or 9.1% data belongs to semantic translation, there is 2 or 9.1% data belong to free translation, and there are 4 or 18.2% data belong to communicative translation. It shows that the most dominant method which is used by the translator is word – for - word translation that there are 11 or 50% data from 2 data half of song lyric “Memories”.